2010
DOI: 10.1523/jneurosci.5722-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Two Concurrent Inhibitory Mechanisms during Response Preparation

Abstract: Inhibitory mechanisms are critically involved in goal-directed behaviors. To gain further insight into how such mechanisms shape motor representations during response preparation, motor evoked potentials (MEPs) elicited by transcranial magnetic stimulation (TMS) and H-reflexes were recorded from left hand muscles during choice reaction time tasks. The imperative signal, which indicated the required response, was always preceded by a preparatory cue. During the postcue delay period, left MEPs were suppressed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

31
234
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(269 citation statements)
references
References 58 publications
31
234
4
Order By: Relevance
“…The most reasonable interpretation of these findings is that slowing in RTs among older individuals is directly associated with a decline in preparatory processes in the dominant hemisphere. Evidence from earlier studies showed that decrease of RTs in short (500-1,000 ms) preparatory periods is accompanied by reduction in CS excitability at the expected onset of the imperative stimulus (Davranche et al 2007;Duque and Ivry 2009;Duque et al 2010;Fujiyama et al 2011;Hasbroucq et al 1997Hasbroucq et al , 1999Hammond 2008, 2009;Tandonnet et al 2003Tandonnet et al , 2010). In the current study, lower suppression of MEPs yet longer RTs in the older individuals may appear seemingly contradictory.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The most reasonable interpretation of these findings is that slowing in RTs among older individuals is directly associated with a decline in preparatory processes in the dominant hemisphere. Evidence from earlier studies showed that decrease of RTs in short (500-1,000 ms) preparatory periods is accompanied by reduction in CS excitability at the expected onset of the imperative stimulus (Davranche et al 2007;Duque and Ivry 2009;Duque et al 2010;Fujiyama et al 2011;Hasbroucq et al 1997Hasbroucq et al , 1999Hammond 2008, 2009;Tandonnet et al 2003Tandonnet et al , 2010). In the current study, lower suppression of MEPs yet longer RTs in the older individuals may appear seemingly contradictory.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, there is no direct evidence to estimate the actual contribution of those brain areas to preparatory suppression of MEPs observed in the present study. Finally, preparatory suppression of MEPs can also be associated with subcortical and/or spinal levels of the motor system (Duque and Ivry 2009;Duque et al 2010;Fujiyama et al 2011;Hammond 2008, 2009;Tandonnet et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, this effect may also be due to an early release of the proactive inhibitory control imposed by the mixed design: the presentation of the spatial cue may help release the inhibition of the superior colliculus on the ocular motoneurons that help to keep the eyes stationary on a visual target (Lo et al 2009). This hypothesis assumes, however, that proactive inhibitory control may be spatially selective (see Duque et al 2010 for an extended discussion about the selectivity of inhibitory mechanisms during response preparation). Such an interpretation is in line with studies suggesting that exogenous visuospatial attention specifically facilitates saccade planning rather than visual target processing (Khan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, predictive cues elicit automatic motor activations, which, in turn, call for response inhibition to prevent false alarms, i.e., to withhold automatic responses to cues Sumner and Husain 2008; see also Allport 1993 for an early discussion). Such cue-related response inhibition probably involves multiple executive and motor mechanisms (Duque et al 2010;Stinear et al 2009;Van Der Lubbe et al 2005). Importantly, this inhibitory control relies not only on postcue responsive mechanisms but also on precue proactive mechanisms that depend on the subject's expectations of the trial structure (Jaffard et al 2007Boulinguez et al 2008Boulinguez et al , 2009Boy et al 2010;Chen et al 2010).…”
mentioning
confidence: 99%
“…Interestingly, the putamen was also more active in the long pro‐cue condition than in the long anti‐cue condition. One possible interpretation of this finding is that inhibition may also be necessary to prevent the premature execution of an already selected response, especially with longer preparation intervals (Duque, Lew, Mazzocchio, Olivier, & Ivry, 2010). …”
Section: Discussionmentioning
confidence: 99%